Early Outcomes Of Living Donor Liver Transplant Recipients In A University Teaching Hospital Of Nepal - Sumita Pradhan; Narendra Maharjan; Deepak Sharma; Bishnu Kandel; Rabin Hamal; Amit Sharma Bhattarai; Pankaj Joshi; Pramesh Sunder Shrestha; Hem Raj Paneru; Subhash P Acharya; Ajit Thapa; Dinesh Chataut; et al. (Journal of Society of Surgeons of Nepal)
Introduction: The burden of chronic liver disease (CLD) is on the rise and liver transplantation remains the best treatment modality for the end stage liver disease (ESLD). Tribhuvan University Teaching Hospital has started doing living donor liver transplantation (LDLT) and we aim to report our experience and early postoperative outcomes of the first 10 living donor liver transplants performed in our institute.